The influence of wheat genotype and environmental factors on gluten index and the possibility of its use as bread quality predictor - Šekularac Andrej (Genetika, 2018)
Gluten index is an indicator of gluten strength as well as a parameter which simultaneously defines its quantity and quality. If compared to the farinographic and extensographic methods, gluten index determining is faster, less complicated and requires smaller amount of flour. The aim of this study has been to determine the significance of the influence of genotype and environmental factors on the value of gluten index and usability of these parameters as indicators and predictors of bread quality. Five local varieties of winter wheat (Simonida, NS 40S, Rapsodija, Pobeda, Zvezdana) were grown in a macro-experiment carried out in three locations (Novi Sad, Čačak, Sombor) during two seasons (2011/2012 and 2012/2013). Gluten index value determination was achieved by using ICC standard method 155 (1996), with a slight modification that included mechanical washing of gluten (Theby). Statistical analysis was performed by using IBM SPSS Statistics 20. Variance analysis revealed a statistically significant effect of genotype on gluten index value, whereas the influence of environmental factors, as well as the interaction of two factors, had no statistical significance. There was no correlation between the values of gluten index and meteorological factors such as average temperature and total precipitation during the phenophase of grain filling, and in the period from the beginning of flowering until the harvest. However, medium-strong negative dependence was found between gluten index and the index of heat stress, as well as between gluten index and the number of days with temperatures above 30°C. Weak negative dependence was recorded between gluten index and bread volume. Based on the value of gluten index, gluten varieties used in our study can be described as strong. Genotype proved to be the only cause of statistically significant variation of gluten index. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. TR 31007]